Development of E-LKPD Assisted by Wizer.Me and Artificial Intelligence on Biological Technology Innovation Material for Class X SMA - Gena Naila Antoni; Zulfarina Zulfarina; Darmawati Darmawati (FKIP - Universitas Riau, 2026)
Teaching and learning the Biological Technology Innovation topic in several senior high schools in Pekanbaru still face various constraints. Students experience difficulties in understanding concepts due to the abstract nature of the material, while the student worksheets (LKPD) used are not yet optimal in terms of content, appearance, and technological integration. As a result, students’ learning motivation and achievement tend to be lower than in other biology topics. This study aimed to develop a high-quality electronic student worksheet (E-LKPD) assisted by Wizer.Me and Artificial Intelligence (AI) for tenth-grade students. The study employed the Research and Development (R&D) method using the ADDIE model up to the development stage. The product was validated by four validators consisting of two Biology Education lecturers and two high school Biology teachers. Limited Trial I involved 10 Biology Education students, while Limited Trial II involved 20 tenth grade high school students. The validation result obtained an average score of 3.79 (highly valid). Limited Trial I and II achieved average scores of 3.81 and 3.82, respectively, both categorized as excellent. The overall quality score was 3.80, indicating that the developed E-LKPD is highly valid, excellent, and feasible for biology learning.